SHOW YOUR WORK!! Solve the polynomial by typing it into a graphing calculator and identifying the zeros. Round to the nearest t

Question

SHOW YOUR WORK!!

Solve the polynomial by typing it into a graphing calculator and identifying the zeros. Round to the nearest tenth.

5x^4-7x^3-5x^2+5x+1=0

SHOW YOUR WORK!!!!!!

in progress 0
Faith 1 month 2021-09-08T14:11:23+00:00 1 Answer 0

Answers ( )

    0
    2021-09-08T14:12:47+00:00

    Answer:

    x = -0.846647 or x = -0.177346 or x = 0.841952 or x = 1.58204

    Step-by-step explanation:

    Solve for x:

    5 x^4 – 7 x^3 – 5 x^2 + 5 x + 1 = 0

    Eliminate the cubic term by substituting y = x – 7/20:

    1 + 5 (y + 7/20) – 5 (y + 7/20)^2 – 7 (y + 7/20)^3 + 5 (y + 7/20)^4 = 0

    Expand out terms of the left hand side:

    5 y^4 – (347 y^2)/40 – (43 y)/200 + 61197/32000 = 0

    Divide both sides by 5:

    y^4 – (347 y^2)/200 – (43 y)/1000 + 61197/160000 = 0

    Add (sqrt(61197) y^2)/200 + (347 y^2)/200 + (43 y)/1000 to both sides:

    y^4 + (sqrt(61197) y^2)/200 + 61197/160000 = (sqrt(61197) y^2)/200 + (347 y^2)/200 + (43 y)/1000

    y^4 + (sqrt(61197) y^2)/200 + 61197/160000 = (y^2 + sqrt(61197)/400)^2:

    (y^2 + sqrt(61197)/400)^2 = (sqrt(61197) y^2)/200 + (347 y^2)/200 + (43 y)/1000

    Add 2 (y^2 + sqrt(61197)/400) λ + λ^2 to both sides:

    (y^2 + sqrt(61197)/400)^2 + 2 λ (y^2 + sqrt(61197)/400) + λ^2 = (43 y)/1000 + (sqrt(61197) y^2)/200 + (347 y^2)/200 + 2 λ (y^2 + sqrt(61197)/400) + λ^2

    (y^2 + sqrt(61197)/400)^2 + 2 λ (y^2 + sqrt(61197)/400) + λ^2 = (y^2 + sqrt(61197)/400 + λ)^2:

    (y^2 + sqrt(61197)/400 + λ)^2 = (43 y)/1000 + (sqrt(61197) y^2)/200 + (347 y^2)/200 + 2 λ (y^2 + sqrt(61197)/400) + λ^2

    (43 y)/1000 + (sqrt(61197) y^2)/200 + (347 y^2)/200 + 2 λ (y^2 + sqrt(61197)/400) + λ^2 = (2 λ + 347/200 + sqrt(61197)/200) y^2 + (43 y)/1000 + (sqrt(61197) λ)/200 + λ^2:

    (y^2 + sqrt(61197)/400 + λ)^2 = y^2 (2 λ + 347/200 + sqrt(61197)/200) + (43 y)/1000 + (sqrt(61197) λ)/200 + λ^2

    Complete the square on the right hand side:

    (y^2 + sqrt(61197)/400 + λ)^2 = (y sqrt(2 λ + 347/200 + sqrt(61197)/200) + 43/(2000 sqrt(2 λ + 347/200 + sqrt(61197)/200)))^2 + (4 (2 λ + 347/200 + sqrt(61197)/200) (λ^2 + (sqrt(61197) λ)/200) – 1849/1000000)/(4 (2 λ + 347/200 + sqrt(61197)/200))

    To express the right hand side as a square, find a value of λ such that the last term is 0.

    This means 4 (2 λ + 347/200 + sqrt(61197)/200) (λ^2 + (sqrt(61197) λ)/200) – 1849/1000000 = (8000000 λ^3 + 60000 sqrt(61197) λ^2 + 6940000 λ^2 + 34700 sqrt(61197) λ + 6119700 λ – 1849)/1000000 = 0.

    Thus the root λ = (-3 sqrt(61197) – 347)/1200 + 1/60 (-i sqrt(3) + 1) ((3 i sqrt(622119) – 4673)/2)^(1/3) + (19 (i sqrt(3) + 1))/(3 2^(2/3) (3 i sqrt(622119) – 4673)^(1/3)) allows the right hand side to be expressed as a square.

    (This value will be substituted later):

    (y^2 + sqrt(61197)/400 + λ)^2 = (y sqrt(2 λ + 347/200 + sqrt(61197)/200) + 43/(2000 sqrt(2 λ + 347/200 + sqrt(61197)/200)))^2

    Take the square root of both sides:

    y^2 + sqrt(61197)/400 + λ = y sqrt(2 λ + 347/200 + sqrt(61197)/200) + 43/(2000 sqrt(2 λ + 347/200 + sqrt(61197)/200)) or y^2 + sqrt(61197)/400 + λ = -y sqrt(2 λ + 347/200 + sqrt(61197)/200) – 43/(2000 sqrt(2 λ + 347/200 + sqrt(61197)/200))

    Solve using the quadratic formula:

    y = 1/40 (sqrt(2) sqrt(400 λ + 347 + sqrt(61197)) + sqrt(2) sqrt(347 – sqrt(61197) – 400 λ + 172 sqrt(2) 1/sqrt(400 λ + 347 + sqrt(61197)))) or y = 1/40 (sqrt(2) sqrt(400 λ + 347 + sqrt(61197)) – sqrt(2) sqrt(347 – sqrt(61197) – 400 λ + 172 sqrt(2) 1/sqrt(400 λ + 347 + sqrt(61197)))) or y = 1/40 (sqrt(2) sqrt(347 – sqrt(61197) – 400 λ – 172 sqrt(2) 1/sqrt(400 λ + 347 + sqrt(61197))) – sqrt(2) sqrt(400 λ + 347 + sqrt(61197))) or y = 1/40 (-sqrt(2) sqrt(400 λ + 347 + sqrt(61197)) – sqrt(2) sqrt(347 – sqrt(61197) – 400 λ – 172 sqrt(2) 1/sqrt(400 λ + 347 + sqrt(61197)))) where λ = (-3 sqrt(61197) – 347)/1200 + 1/60 (-i sqrt(3) + 1) ((3 i sqrt(622119) – 4673)/2)^(1/3) + (19 (i sqrt(3) + 1))/(3 2^(2/3) (3 i sqrt(622119) – 4673)^(1/3))

    Substitute λ = (-3 sqrt(61197) – 347)/1200 + 1/60 (-i sqrt(3) + 1) ((3 i sqrt(622119) – 4673)/2)^(1/3) + (19 (i sqrt(3) + 1))/(3 2^(2/3) (3 i sqrt(622119) – 4673)^(1/3)) and approximate:

    y = -1.19665 or y = -0.527346 or y = 0.491952 or y = 1.23204

    Substitute back for y = x – 7/20:

    x – 7/20 = -1.19665 or y = -0.527346 or y = 0.491952 or y = 1.23204

    Add 7/20 to both sides:

    x = -0.846647 or y = -0.527346 or y = 0.491952 or y = 1.23204

    Substitute back for y = x – 7/20:

    x = -0.846647 or x – 7/20 = -0.527346 or y = 0.491952 or y = 1.23204

    Add 7/20 to both sides:

    x = -0.846647 or x = -0.177346 or y = 0.491952 or y = 1.23204

    Substitute back for y = x – 7/20:

    x = -0.846647 or x = -0.177346 or x – 7/20 = 0.491952 or y = 1.23204

    Add 7/20 to both sides:

    x = -0.846647 or x = -0.177346 or x = 0.841952 or y = 1.23204

    Substitute back for y = x – 7/20:

    x = -0.846647 or x = -0.177346 or x = 0.841952 or x – 7/20 = 1.23204

    Add 7/20 to both sides:

    Answer: x = -0.846647 or x = -0.177346 or x = 0.841952 or x = 1.58204

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )